IMF Committee on Balance of Payments Statistics : Annual Report 2012. (Balance of Payments Statistics; Balance of Payments Statistics ;, 2013)
The Annual Report of the IMF Committee on Balance of Payments Statistics (Committee) for 2012 provides an overview of recent trends and discrepancies in global balance of payments statistics, summarizes the Committee's work program during 2012, and reviews the issues the Committee plans to address in the coming year.